Physicochemical stability of azacitidine suspensions at 25 mg/mL in polypropylene syringes stored under different conditions of storage - Trambloy Quentin; Vigneron Jean; Clarot Igor; Blaise Franck; D'Huart Elise; Demoré Béatrice (De Gruyter, 2022)
Azacitidine is a pyrimidine nucleoside analogue whose stability is temperature dependent. Numerous publications have studied the stability of this drug with discordant results. The purpose of this work is to study the stability of azacitidine suspensions under different conditions to allow preparation in advance: vials stored at room temperature or between 2 and 8 °C, reconstituted with refrigerated water for injection (WFI) or frozen/thawed WFI, azacitidine suspensions stored at room temperature, 2-8 °C or at −20 °C. The feasibility of a vented ChemoClave® Spike vial was also tested to reconstitute and collect azacitidine to aid the preparation stage.